Analysis of Vocational School Students’ Entrepreneurial Interest: The Role of Knowledge, Motivation, and Self-Efficacy - Nurhayannah, Afifah; Zulaihati, Sri; Adha, Maulana Amirul (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Examining entrepreneurial knowledge, achievement motivation, self-efficacy, and entrepreneurial interest in students at SMKN 51 Jakarta is the goal of this study. It also seeks to ascertain the relationship between entrepreneurial knowledge, self-efficacy, entrepreneurial interest, and achievement motivation at SMKN 51 Jakarta. The present study utilizes a quantitative research methodology. Primary data collection was done by a survey method employing a proportional random sample strategy. 324 students made up the population for this study, and the sample size of 180 was determined using Slovin's formula. Multiple regression analysis and correlation testing were performed on the data using SPSS version 27. The study's findings suggest that self-efficacy and entrepreneurial knowledge positively and significantly affect entrepreneurial interest. At SMKN 51 Jakarta, however, entrepreneurial curiosity is positively influenced by accomplishment motivation, albeit not significantly. Furthermore, at SMKN 51 Jakarta, entrepreneurial desire is simultaneously influenced by self-efficacy, accomplishment motivation, and entrepreneurial expertise.